2013
DOI: 10.1186/2192-1962-3-18
|View full text |Cite
|
Sign up to set email alerts
|

Social design feedback: evaluations with users in online ad-hoc groups

Abstract: Social design feedback is a novel approach to usability evaluation where user participants are asked to comment on designs asynchronously in online ad-hoc groups. Two key features of this approach are that (1) it supports interaction between user participants and development team representatives and (2) user participants can see and respond to other participants' comments. Two design cases, involving 250 user participants, were studied to explore the output of social design feedback and investigate the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Compared with PAACP and SECSPP, our scheme achieves more functionality and satisfies the security features required by VANETs. Future research can focus on the many commercial applications [19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with PAACP and SECSPP, our scheme achieves more functionality and satisfies the security features required by VANETs. Future research can focus on the many commercial applications [19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…The qualitative evaluation module provides the comparison results made by experts in qualitative manner. The qualitative evaluation module has a request button and a panel for the responses from experts [5]. The data control interface deals with data and communication interface and all data are managed in XML format.…”
Section: Related Workmentioning
confidence: 99%
“…Results from previous study [26] suggested that assessment should be based on not only medical diagnosis but also impairment and disability for long-term care. Classification systems developed for LTC should use more sophisticated methods than those used in other care areas.…”
Section: Resident-oriented Assessmentmentioning
confidence: 99%
“…Traditional pigeonholed resident placement constitutes a depersonalised care service and is deemed not socially acceptable [26]. Classifying residents into categories by their care needs would be useful for resident placement decisions and would reflect humanistic considerations.…”
Section: Classifying Residents By Types Of Carementioning
confidence: 99%